Modeling and optimization for prediction of moisture content, drying rates and moisture ratio - Shrivastav, Shivmurti; Kumbhar, B. K. (International Journal of Agricultural and Biological Engineering, 2009)
There were needs to develop some preservation technique to enhance the shelf life of Paneer because it is highly perishable in nature at ambient conditions. Drying can be one of the methods to increase shelf life of paneer. This study was undertaken to dry 1.5 cm3 paneer at 62, 72 and 82